Assessment of the Knowledge, Attitude, and Performance of Female Junior High School Students of Neka, Iran, about Iron Deficiency Anemia in 2016 - Seyed Aboalhassan naghibi; mahbubeh ahmadi; farzaneh afkhaminia (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: Anemia is one of the most common nutritional disorders in the world and is often associated with iron deficiency. Iron deficiency anemia causes waste of educational resources and health care, reduction of productivity through increased mortality, and finally the reduction of physical and psychological capacity in a large part of society. Regarding this, the present study was conducted to determine the knowledge, attitude, and practice of female junior high school students in Neka city, Iran, about iron deficiency in 2016. Methods: This cross-sectional study was conducted on 480 junior high school students in Neka, who were educating during 2016. The study population was selected through multi-stage sampling technique. The data collection tools included a questionnaire covering demographic data and assessing the knowledge (18 items), attitude (14 items), and  performance (9 items) about iron deficiency. The collected data were analyzed using descriptive and inferential statistics, including independent t-test and one-way ANOVA, in SPSS software (version 20). Results: According to the results, the mean age of the students was 12.91±0.79. In this study, 17.1%, 38.3%, and 1.9% of the students had good level of  knowledge, attitude, performance regarding iron deficiency, respectively. The results also revealed a significant relationship between paternal education level and knowledge score (P=0.001). Furthermore, maternal education showed a significant relationship with knowledge (P=0.001) and performance (P=0.019). There was also a significant difference between the different levels of paternal occupation in terms of the mean score of knowledge (P=0.001) and performance (P=0.002). However, maternal occupation demonstrated no significant relationship with knowledge, attitude, and performance.Conclusion: As the findings indicated, the knowledge of the majority of students about iron deficiency was at a moderate level; however, most of them had a poor performance in this regard. Therefore, in line with the Health Promoting School programs, the design of family-centered and school-based interventional programs is recommended to empower parents, students, and school about iron deficiency anemia.